Behavioural and neurocognitive responses to sad facial affect are attenuated in patients with mania. - Lennox, B; Jacob, R; Calder, A; Lupson, V; Bullmore, E (2004)
BACKGROUND: The processing of facial emotion involves a distributed network of limbic and paralimbic brain structures. Many of these regions are also implicated in the pathophysiology of mood disorders. Behavioural data indicate that depressed subjects show a state-related positive recognition bias for faces displaying negative emotions. There are sparse data to suggest there may be an analogous, state-related negative recognition bias for negative emotions in mania. We used functional magnetic resonance imaging (fMRI) to investigate the behavioural and neurocognitive correlates of happy and sad facial affect recognition in patients with mania. METHOD: Functional MRI and an explicit facial affect recognition task were used in a case-control design to measure brain activation and associated behavioural response to variable intensity of sad and happy facial expressions in 10 patients with bipolar I mania and 12 healthy comparison subjects. RESULTS: The patients with mania had attenuated subjective rating of the intensity of sad facial expressions, and associated attenuation of activation in the subgenual anterior cingulate and bilateral amygdala, with increased activation in the posterior cingulate and posterior insula. No behavioural or neurocognitive abnormalities were found in response to presentation of happy facial expressions. CONCLUSIONS: Patients with mania showed a specific, mood-congruent, negative bias in sad facial affect recognition, which was associated with an abnormal profile of brain activation in paralimbic regions implicated in affect recognition and mood disorders. Functional imaging of facial emotion recognition may be a useful probe of cortical and subcortical abnormalities in mood disorders.